The Effect of Green Building Application to Property Value - Fitri Rahmawati; Purwanita Setijanti; Christiono Utomo (IPTEK Journal of Proceedings Series, 2015)
The green building concept is one of the solution for the next sustainable development. One of the biggest barriers is the feasibility of financial return. This research is conducted to determine the influence of the green building aspects application towards the property value of high rise building that seen from the design and material aspects in Surabaya. This study, conducted by a survey research using questionnaires for data collection, and regression analysis. There are ten aspects that its use may increase the property value, wich are the horizontal massing design, secondary skin, smart lighting systems, grey-water systems, green roof, lightweight concrete, photovoltaic systems, smart lighting systems, air conditioner with VRV systems, gray-water systems, Low-E glazing, low VOC paint wall, and green roof.